Curriculum Transformation: A Qualitative Case Study Of Outcome-Based Education Implementation In The Islamic Education Management Study Program - Izzatun Illiyyin; Na’imah Na’imah; Anas Azhar Nasim; Nihayatuzzain Nihayatuzzain; Wiedya Listrina (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Digital transformation has changed the global education paradigm, requiring adaptive, responsive, and outcome-oriented curriculum. In Indonesia, the implementation of Outcome-Based Education (OBE) has become the main strategy to ensure graduates have 21st-century competencies relevant to industry and community demands. This study aims to (1) describe the transformation of the education curriculum in Indonesia, (2) analyze the implementation of OBE in the Master's Program in Islamic Education Management (MPI) at UIN Sunan Kalijaga, and (3) identify the challenges and opportunities of implementing OBE in the digital era. This study employs a descriptive qualitative approach with data collection through interviews and a review of current literature. The implementation of OBE in MPI began in 2024 through faculty workshops and curriculum standardization, including the development of vision and mission statements, graduate profiles, and Graduate Learning Outcomes (GLOs). The main challenges include varying levels of digital competence among faculty members, resistance to change, and limited technical support. On the other hand, the digital era opens opportunities for increased scientific publications, research and mentoring efficiency, and real-time monitoring of learning outcomes. The findings of this study provide practical guidelines for program administrators and policymakers in optimizing OBE implementation, through strengthening human resource capacity, improving infrastructure, and integrating learning technology.